Challenge and Threat: A Critical Review of the Literature and an Alternative Conceptualization - Uphill, Mark A.; Rossato, Claire J. L.; Swain, Jon; O’Driscoll, Jamie (Frontiers in Psychology, 2019)
Prompted by the development of the Theory of Challenge and Threat States in Athletes (Jones et al, 2009), recent years has witnessed a considerable increase in research examining challenge and threat in sport. This manuscript provides a critical review of the literature examining challenge and threat in sport, tracing its historical development and some of the current empirical ambiguities. In an attempt to reconcile some of these ambiguities, and utilising neurobiological evidence associated with approach- and avoidance-motivation (cf. Elliot & Covington, 2001), this paper draws upon the Evaluative Space Model (ESM: Cacioppo et al., 1997) and considers the implications for understanding challenge and threat in sport. For example, rather than see challenge and threat as opposite ends of a single bipolar continuum, the ESM implies that individuals could be (1) challenged, (2) threatened, (3) challenged and threatened, or (4) neither challenged or threatened by a particular stimulus. From this perspective it could be argued that the appraisal of some sport situations as both challenging and threatening could be advantageous, whereas the current literature seems to imply that the appraisal of stress as a threat is maladaptive for performance. In drawing upon the ESM, we outline the Evaluative Space Approach to Challenge and Threat and provide several testable hypotheses for advancing understanding of challenge and threat (in sport). We also outline a number of cardiovascular and experiential measures that can be used to examine these hypotheses. In sum, this paper provides a significant theoretical, empirical and practical contribution to our understanding of challenge and threat (in sport).